2013
DOI: 10.1007/s40139-013-0023-x
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Homeostasis in Acute Organ Failure

Abstract: The kidneys compose approximately 0.5% of the body mass but consume about 10% of the oxygen in cellular respiration. This discordance is due to the high energy demands on the kidney for reabsorption of filtered blood components and makes the kidney sensitive to mitochondrial stress, the primary source of cellular ATP. Regardless of the etiology, acute kidney injury (AKI) almost always involves aspects of mitochondrial dysfunction. Recent evidence from experimental models suggests that preserving mitochondrial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 88 publications
(118 reference statements)
3
75
0
Order By: Relevance
“…Inhibiting phosphorylated ERK1/2 pre-surgery attenuated the PGC-1␣ and NRF1 mRNA decreases and prevented an increase in serum creatinine. We have previously shown that PGC-1␣ is rapidly decreased following diverse models of AKI in mice and rats, and these results implicate ERK1/2 as the mediator behind this transcriptional suppression (10,11,32).…”
Section: Erk1/2 Regulates Pgc-1␣mentioning
confidence: 80%
See 2 more Smart Citations
“…Inhibiting phosphorylated ERK1/2 pre-surgery attenuated the PGC-1␣ and NRF1 mRNA decreases and prevented an increase in serum creatinine. We have previously shown that PGC-1␣ is rapidly decreased following diverse models of AKI in mice and rats, and these results implicate ERK1/2 as the mediator behind this transcriptional suppression (10,11,32).…”
Section: Erk1/2 Regulates Pgc-1␣mentioning
confidence: 80%
“…Previous studies demonstrated that rapid and persistent disruption of mitochondria homeostasis is an important contributor to the pathology of renal ischemia/reperfusion (IR) injury (10,11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In experimental models of AKI, abnormal mitochondrial biogenesis, fission/fusion, and autophagy have been characterized and recovery of mitochondrial functions was found to be important for function of the kidney 11 . Ischemia-reperfusion injury in AKI contributes to fragmentation of mitochondria and processes leading to cell death 10 .…”
Section: Acute Kidney Injurymentioning
confidence: 99%
“…Dysfunction of mitochondria caused by inherited mitochondrial cytopathies or acquired defects of proteins involved in mitochondrial metabolic pathways contributes to the pathophysiology of acute and chronic renal disorders 7 . Disruption of mitochondrial energetic metabolism [7][8][9] and morphology 10,11 is recognized as important contributors to tubular dysfunction in acute kidney injury (AKI). Increased production of ROS triggered by hypoxia in mitochondria during sepsis leads to kidney dysfunction and contributes to dysfunction of organs.…”
Section: Introductionmentioning
confidence: 99%